LURIGANCHO, A YCHSMA CURACAZGO ON THE RIGHT MARGIN OF THE RIMAC LOWER VALLEY - Abanto Ll., Julio (2008)
The studies about the approach of a curacazgo mamed Lurigancho or Ruricanchu, started in 1996. Ten years later the gotten dates let us recognize the definition of a territorial unit for a political space developed probably from. The later pre-ceramic period to the Inka presence in the valley. This territorial unit is the actual Quebrada Canto Grande, located on the right side of the Rimac river. Canto Grande, not only had space economically productive, demarcated for and irrigation channel. In addition to this, it had a serie of architectural complexes, Showing ranks and suggesting a role in the control and manage of its resources. The archeological material that were observed for the later periods match to the ceramic tradition defined as Ychsma; in the some way its architectural expression has similarities in other peaces set of the valley. The revision of ancient documents refer the Lurigancho as a group which native population formed part of the San Juan Bautista de Lurigancho reduction during the colony. In shot, our study set the Quebrada Canto Grande as the life space of the Lurigancho curacazgo and identifies the Mangomarca archeological complex as its political seat.